First invasion of Ambrostoma superbum (Thunberg, 1787) (Coleoptera, Chrysomelidae) in Western Siberia - Legalov, Andrei A.; Reshetnikov, Sergei V. (Acta Biologica Sibirica, 2022)
The first invasion of Ambrostoma superbum (Thunberg, 1787) (Chrysomelidae: Chrysomelinae, Doryphorini) from Novosibirsk (Novosibirskaya Oblast) is recorded. The distribution map, illustrations and redescription of this species are presented. This species causes significant damage to Ulmus pumila L.